2019
DOI: 10.1111/apt.15395
|View full text |Cite
|
Sign up to set email alerts
|

Depression is associated with non‐alcoholic fatty liver disease among adults in the United States

Abstract: Background: Currently, the relationship between depression and non-alcoholic fatty liver disease (NAFLD) is not clearly defined. Aim:To determine whether depression is associated with NAFLD and NAFLD-related advanced fibrosis in a large population sample. Methods: We performed a cross-sectional analysis using the 2007-2016 National Health and Nutrition Examination Survey database among adults (20 years or older) in the United States (US). Depression and functional impairment due to depression were assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 44 publications
2
70
1
2
Order By: Relevance
“…Patients with significant fibrosis also employed maladaptive strategies, such as disengagement, to a greater extent in comparison with NASH patients without significant fibrosis, and fewer adaptive strategies such as active coping or acceptance. The results for mental health confirm the relationship between fibrosis and depression already noted previously by Weinstein et al (15), Youssef et al (7), and Tomeno et al (16) and therefore contradict the conclusion of Kim et al (17). In brief, the main findings of this study verified that there are differences in the QoL, mental health, and coping strategies of NAFLD patients depending on the perceived social support and histological fibrosis and confirm that the relevant variables predicting a worse disease-specific QoL in these patients are significant fibrosis, female sex, greater anxiety and depressive symptoms, and worse physical and mental health-related QoL.…”
Section: Cope-28supporting
confidence: 73%
See 1 more Smart Citation
“…Patients with significant fibrosis also employed maladaptive strategies, such as disengagement, to a greater extent in comparison with NASH patients without significant fibrosis, and fewer adaptive strategies such as active coping or acceptance. The results for mental health confirm the relationship between fibrosis and depression already noted previously by Weinstein et al (15), Youssef et al (7), and Tomeno et al (16) and therefore contradict the conclusion of Kim et al (17). In brief, the main findings of this study verified that there are differences in the QoL, mental health, and coping strategies of NAFLD patients depending on the perceived social support and histological fibrosis and confirm that the relevant variables predicting a worse disease-specific QoL in these patients are significant fibrosis, female sex, greater anxiety and depressive symptoms, and worse physical and mental health-related QoL.…”
Section: Cope-28supporting
confidence: 73%
“…In addition, the relationship between fibrosis and mental health in NAFLD patients is not clear either. Several studies have found an association between the presence of fibrosis and anxiety and depressive symptoms (7,15,16), while Kim et al (17) found no relationship. Furthermore, female sex has been associated with a worse physical and mental QoL than does male sex (2,18).…”
Section: Introductionmentioning
confidence: 96%
“…(14) Another recently published study derived from the NHANES database demonstrated an association between NAFLD and the prevalence of depression. (11) On multivariate analysis, a significant association between depression and NAFLD defined by ultrasound but also with the hepatic steatosis index was observed in this cohort study. (11) The current large-scale analysis confirmed an independent impact of NAFLD on the incidence of depression in, to the best of our knowledge, the largest population-based cohort with a nationally representable sample of German adults.…”
Section: %supporting
confidence: 49%
“…(9,10) A recent study using the National Health and Nutrition Examination Survey (NHANES) observed an association between depression and NAFLD in the United States. (11) However, other recent studies produced conflicting evidence on the potential relation between NAFLD and depression. (12,13) Anxiety is another frequent psychiatric disorder in the Western world.…”
mentioning
confidence: 99%
“…The recent study from Kim et al took a different approach with the NHANES database: the Fatty Liver Index, the hepatic steatosis index and the US Fatty Liver Index were used to identify patients with NAFLD, and FIB‐4 to stage the degree of fibrosis. Depression was present in over 10% of the entire cohort and shared risk factors with NAFLD.…”
mentioning
confidence: 99%